Cumprimento das decisões do sistema de solução de controvérsias da Organização Mundial do Comércio: análise das medidas de indução e das propostas para seu aprimoramento sob a perspectiva dos países em desenvolvimento - Árabe Neto, Abrão Miguel (2008)
The WTO World Trade Organization dispute settlement system stands out as one of the most significant developments in contemporary international law. Created with strong jurisdictional features, it serves as the main forum for the resolution of conflicts of interest in international trade. Success in this task, however, is dependent upon the degree of compliance achieved by its decisions. As a consequence, it is important to assess whether WTO rules provide suitable instruments in order to secure implementation, especially when opposed by respondents. Guided by this challenge, this paper seeks to examine the current performance of WTO enforcement tools, particularly from the perspective of developing countries. After exposing the shortcomings of these instruments, the analysis focuses on its reform proposals, aiming to identify the most viable alternatives for enhancement